Design and implementation of planting information service system based on GIS. Issue 1 (May 2020) - Jia, Hu; Zhenyu, Zhao; Qiulan, Wu; Feng, Zhang; Zhenyu, Si; Cuihong, Lu; Xia, Geng
Abstract: The information service of planting features various service content; scattered and isolated information; diversity of data source and format, as well as high cost of system operation. Since agricultural production decision-making and management have diversified demands on scientific and technological service, a GIS-based planting information service system was designed and developed. This system integrates the geographic information data and planting service thematic data, which is based on multi-source heterogeneous data integration, GIS spatial analysis, responsive framework and other technologies. Through various terminals such as computers and mobile phones, the system provides land circulation information inquiry, soil fertility analysis, crop variety selection, production materials purchase, agricultural technology guidance, labor employment recruitment, agricultural product sales and other comprehensive information services of the whole planting life cycle. It guides farmers to plant rationally, and helps farmers resolve the issues relating to information islands and the information shortage problem in production and life by "one-stop", and increase the famers' income. It can also provide decision-making gist for agricultural administrative departments to adjust planting structure, optimize the rural industrial layout and related policy formulation. Through demonstration in Zhucheng, a new model for serving "agriculture, rural areas and farmers" with surveying and mapping geographic information has been formed in terms of resource integration, geospatial data services, and service information access.